The knee injuries in skiing: Mechanisms and assessment - Mayr, H. O.; Chèze, L. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study is to describe the main mechanisms of knee injuries in skiing, and especially the dominant role of anterior cruciate ligament in these injuries. To complete classical clinical tests of ligamentous laxity and help defining the appropriate time to return to sports after an anterior cruciate ligament reconstruction, accurate 3D kinematic assessment of the weight-bearing knee joint is essential. Current limits of such an assessment are described. Then recent studies of patients with anterior cruciate ligament deficient and reconstructed, using a tibio femoral tracking device specially designed to analyse the kinematics of the knee, are presented.